Acute kidney injury due to povidone-iodine ingestion: A case report. Issue 48 (December 2017) - Kim, Chang Seong; Kim, Sung Sun; Bae, Eun Hui; Ma, Seong Kwon; Kim, Soo Wan
Abstract: Rationale: Povidone-iodine is a broad-spectrum antiseptic applied topically to treat wounds and prevent their infection. There have been several case reports of acute kidney injury (AKI) in burn patients after povidone-iodine irrigation and in patients receiving the substance as a sclerotherapy agent for management of lymphocele after renal transplantation. However, biopsy-confirmed AKI after ingestion of povidone-iodine has not previously been described. Patient concerns: A 47-year-old man who had apparently ingested povidone-iodine solution and presented with nausea, vomiting, and reduced urine output. Laboratory data revealed blood urea nitrogen of 124 mg/dL, serum creatinine of 6.3 mg/dL, impaired liver function, and leukocytosis. Urine iodine/creatinine ratio was markedly elevated. Diagnoses: Acute tubular necrosis and interstitial nephritis secondary to povidone-iodine ingestion. Interventions: The patient was admitted to the intensive care unit and underwent continuous venovenous hemodiafiltration. Kidney biopsy showed acute tubular necrosis and interstitial nephritis. Unstained sections showed tan objects in the tubular lumina that were suspected to be povidone-iodine casts. Corticosteroid therapy (1 mg/kg/day) was started after kidney biopsy. Outcomes: Renal function recovered after hemodialysis and corticosteroid medication, but not completely. Lessons: We have reported the first case of biopsy-confirmed AKI accompanied by increased urine iodine concentration following povidone-iodine ingestion.